Entropy Growth Is the Manifestation of Spontaneity. (7th December 2014) - Wang, Lin-Shu
Abstract : Every student of thermodynamics grasps entropy growth in terms of dissipation of energy. The real nature of energy and entropy is subtle. This critical review of the evolution of thermodynamic thought uncovers the remarkable advance on our understanding of energy made by Kelvin with his dissipation of energy proposition. Maxwell and Planck, however, pointed out that dissipation of energy does not exhaust growth of entropy (i.e., the idea of spontaneity), and in fact, as it is shown here, Kelvin's proposition of dissipation of energy (1852) is subsumed under the principle of the increase of entropy (Clausius, 1865). It is necessary, therefore, for thermodynamics to become a coherent conceptual system, to introduce spontaneity as an independent concept. Instead of the heat-work dyad framework, the introduction of spontaneity entails energy transformation to be viewed in terms of a triad framework of heat (from the reservoir)-work-spontaneity. Spontaneity is the new energy in the triad framework, and it is also clear that energy commodity (fungible energy or energy carriers) is only one kind of spontaneity, stock spontaneity ; the other kind is ongoing spontaneity, the consideration of which is necessary for comprehending problems of homeostasis in both the organic and inorganic worlds.